Evaluation of Problem Based Gamification Learning (PBGL) Model on Critical Thinking Ability with Artificial Intelligence Approach Integrated with ChatGPT API: An Experimental Study - Remerta Noni Naatonis; Rusijono Rusijono; Miftakhul Jannah; Edwin Ariesto Umbu Malahina (Qubahan Academic Journal)
This research evaluates the effectiveness of the PBGL model integrated with Artificial Intelligence (A.I) using the ChatGPT API to improve students' critical thinking skills. The main problems faced are the limited time of the lecturer in delivering the material, the lack of reference material, and the low motivation of students. This research used an experimental method involving 520 students from Timor Leste (Cova-Lima and Dili districts) and Indonesia (East Java and East Nusa Tenggara provinces) studying Python, Java, and Web programming. Participants were divided into control (n=260) and experimental (n=260) groups. Key challenges included integration of the ChatGPT API, implementation of A.I-based automated feedback, and maintaining consistency and fairness in testing. The evaluation results showed significant improvement in critical thinking skills in the experimental group across all topics. For the Python topic, the experimental group had an average improvement of 20.75 points, compared to 8.20 points in the control group, with an average difference of 12.55 points. On the Java topic, the experimental group increased by an average of 25.58 points, while the control group only 7.86 points, with an average difference of 17.72 points. In the Web Programming Languages topic, the experimental group showed an average increase of 23.74 points, compared to 8.58 points in the control group, with an average difference of 15.16 points. These findings confirm that the contribution of A.I and ChatGPT integration in the PBGL model can improve critical thinking, provide automatic feedback, and increase student motivation. This research has the potential to be a reference in digital curriculum design with generative A.I approaches such as ChatGPT API, showing that A.I can enrich learning materials, personalized materials and provide flexibility for students and teachers in the digital era.